Detection of Interloper Using Sensors - M. Prabu, S. Janani, C. Maneesha, K. Ramya (International Journal of Control and Automation, 2020)
This study represents a concept by which one can identify trespassers. The concept here is radar sensors along with buried optic fiber sensor, the radar sensor detects the movement of any object and alerts the surrounding also it notifies the respective group of people, the identification manner of the interloper is invariant to the weight and speed of the object (human or animals) and sort of the dirt, the profundity at which the fiber is secured, ecological conditions nearer to the fiber. The radar sensor gives common penetration limit through an atmosphere condition and can be used in day or night time, it uses electromagnetic waves that doesn't require a solid medium. The optic fiber sensor is a lightweight, small in size, low weakening, invulnerability to electromagnetic obstruction, wide transfer speed and encompassing toughness. This idea can be used at various locations such as at the border of two countries, and other legally restricted areas. At increasing levels of illegal happenings, it will be of immense benefit to develop a simple and cost handy device to identify unwanted trespassers.